Hubungan Intensitas Publikasi dan Citra Lembaga Pendidikan dengan Animo Siswa yang Memilih Sekolah di SMK Negeri Kabupaten Malang - Alfin Nur Indah Sari; Ali Imron; Imron Arifin; Alfin Nur Indah Sari; Ali Imron (Universitas Negeri Malang, 2023)
Abstract: The study aims to know (1) a picture of publication intensity, (2) an image of an educational institution's image, (3) an overview of the students' interest in choosing a school at SMK Negeri Malang, (4) the relationship between publication intensity and student's interest, (5) an image relationship educational institutions with student interest, (6) the relationship between publication intensity and the image of educational institutions with student interest. This research uses a quantitative approach with a descriptive-correlational research model. The research instrument used in this study was a questionnaire. The subjects who became the population in this study were students of class X State Vocational School. The results showed that the intensity of publications, the image of educational institutions and student interest were in the medium category. There is a relationship between the intensity of publications and the image of educational institutions with the interest of students who choose schools. Abstrak: Penelitian bertujuan untuk mengetahui (1) gambaran intensitas publikasi, (2) gambaran citra lembaga pendidikan, (3) gambaran animo siswa yang memilih sekolah di SMK Negeri Kabupaten Malang, (4) hubungan antara intensitas publikasi dengan animo siswa, (5) hubungan citra lembaga pendidikan dengan animo siswa, (6) hubungan intensitas publikasi dan citra lembaga pendidikan dengan animo siswa. Penelitian ini menggunakan pendekatan kuantitatif dengan model penelitian deskriptif-korelasional. Instrumen penelitian yang dipergunakan dalam penelitian ini berupa angket. Subjek yang menjadi populasi dalam penelitian ini adalah siswa SMK Negeri kelas X. Hasil penelitian menunjukkan bahwa intensitas publikasi, citra lembaga pendidikan dan animo siswa berada pada kategori sedang. Terdapat hubungan antara intensitas publikasi dan citra lembaga pendidikan dengan animo siswa yang memilih sekolah.